2019
DOI: 10.3389/fsurg.2019.00053
|View full text |Cite
|
Sign up to set email alerts
|

Free Flap Selection and Outcomes of Soft Tissue Reconstruction Following Resection of Intra-oral Malignancy

Abstract: Introduction: Surgery to resect intra-oral malignancy is a well-established mode of primary treatment. The tissue requirement in this area is for a thin, pliable flap with minimal bulk and this has historically been provided by free tissue transfer with a radial forearm free flap (RFFF). More recently, a role for the anterolateral thigh free flap (ALTFF) has been described, although in populations with a westernized diet, body habitus may preclude use of an ALTFF due to flap thickness, relative to a radial for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
12
1
Order By: Relevance
“…At this location, the diameter of the perforator is small and can be easily damaged by traction kinking Nevertheless, ALTFF has the advantage of harvesting a greater amount of tissue than RFFF, as well as the direct primary closure is possible if the width of donor site is less than 8 cm. Several studies favoring the benefits of ALTFF reported no significant difference in flap survival rates between RFFF and ALTFF [15][16][17][18]; however, in this study, the success rate of RFFF (98.9%) was significantly higher than of ALTFF (94.5%) (p< 0.01). Mandibular reconstruction was performed using fibular OCFF (33 cases) or DCIA osteocutaneous flaps (2 cases); two fibular OCFF failed.…”
Section: Discussioncontrasting
confidence: 84%
“…At this location, the diameter of the perforator is small and can be easily damaged by traction kinking Nevertheless, ALTFF has the advantage of harvesting a greater amount of tissue than RFFF, as well as the direct primary closure is possible if the width of donor site is less than 8 cm. Several studies favoring the benefits of ALTFF reported no significant difference in flap survival rates between RFFF and ALTFF [15][16][17][18]; however, in this study, the success rate of RFFF (98.9%) was significantly higher than of ALTFF (94.5%) (p< 0.01). Mandibular reconstruction was performed using fibular OCFF (33 cases) or DCIA osteocutaneous flaps (2 cases); two fibular OCFF failed.…”
Section: Discussioncontrasting
confidence: 84%
“…15,16 Radial forearm free flap, which was used as the first free flap for intraoral defects in 1983, 17 has been used for many years because of some advantages such as thinness, pliability, reliable anatomy, and long pedicle. 18 However, sacrificing a major artery and donor site problems 19 are the main drawbacks that resulted in choosing different types of flaps. Superficial circumflex iliac artery perforator flap is among free flap options with easy donor site management.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of microvascular anastomosis technology, grafting with a vascularized free flap has made it possible to repair and functionally restore tissue defects after maxillofacial trauma or tumor resection (15). Currently, the commonly used vascularized free flaps in the clinical practice include a radial forearm flap, deep inferior epigastric artery perforator flap, thoracodorsal artery perforator flap, deep circumflex iliac artery perforator flap, and ALT flap (16). Among them, the ALT flap has become the first choice to repair the head and neck, extremity, and truck defects in many medical centers (17,18).…”
Section: Discussionmentioning
confidence: 99%